Mortality from external causes in late adolescence and early adulthood by gestational age and sex: a population-based cohort study in four Nordic countries - Josephine Funck Bilsteen; Signe Opdahl; Anna Pulakka; Per Ivar Finseth; Weiyao Yin; Kristine Pape; Jorun Schei; Johanna Metsälä; Anne-Marie Nybo Andersen; Sven Sandin; Eero Kajantie; Kari Risnes (BMC Medicine)
Abstract Background External causes of death, such as accidents, substance use, and suicide, contribute substantially to mortality during adolescence and early adulthood and show marked sex differences. Individuals born preterm are at increased risk of mental disorders, and impaired cognitive and executive functions, potentially increasing their vulnerability to death from external causes. We investigated sex-specific associations between gestational age at birth and mortality from external causes during late adolescence and early adulthood. Methods Individual level data from national health registries in Denmark (1978–2001), Finland (1987–2003), Norway (1967–2002), and Sweden (1974–2001) were linked to form nationwide cohorts. In total, 6,924,697 participants were followed from age 15 years to a maximum of 50 years in 2016–2018. Gestational age was categorized as “very/moderately preterm” (23–33 weeks), “late preterm” (34–36 weeks), “early term” (37–38 weeks), “full term” (39–41 weeks), and “post term” (42–44 weeks). Outcomes were mortality from external causes overall and from the largest subgroups transport accidents, suicide, and drugs or alcohol. We estimated sex-specific hazard ratios (HRs), with full term as the reference, and pooled each country’s estimates in meta-analyses. Results Across gestational ages mortality was higher for males than females. Individuals born very/moderately preterm had higher mortality from external causes, with HRs 1.11 (95% confidence interval [CI] 0.99–1.24) for males and 1.55 (95% CI 1.28–1.88) for females. Corresponding estimates for late preterm born were 1.11 (95% CI 1.04–1.18) and 1.15 (95% CI 1.02–1.29), respectively. Those born very/moderately preterm had higher mortality from transport accidents, but precision was low. For females, suicide mortality was higher following very/moderately preterm birth (HR 1.76, 95% CI 1.34–2.32), but not for males. Mortality from drugs or alcohol was higher in very/moderately and late preterm born males (HRs 1.23 [95% CI 0.99–1.53] and 1.29 [95% CI 1.16–1.45], respectively) and females (HRs 1.53 [95% CI 0.97–2.41] and 1.35 [95% CI 1.07–1.71], respectively, with some heterogeneity across countries). Conclusions Mortality from external causes overall was higher in preterm than full term born among both males and females. A clear sex difference was seen for suicide, where preterm birth was a risk factor in females, but not in males.